The effect of unemployment on the prevalence of HIV/AIDS epidemic in relation to corporate social investing - Masanabo, Vusumuzi Joseph Godfrey (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.